PELATIHAN PEMBUATAN E-COMATS BERBASIS ETHNOMATHEMATICS BERBANTUAN AR UNTUK MENINGKATKAN LITERASI TEKNOLOGI GURU - Novferma Novferma; Nizlel Huda; Destrinelli Destrinelli; Bella Arisha; Nurul Hidayah (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTThe limited technological literacy and teachers’ ability to integrate digital learning media remain major challenges in implementing the Merdeka Curriculum. Addressing this issue, this study introduced the development of E-COMATS (Ethnomathematics Comic Augmented Reality for Teaching and Learning) grounded in local cultural contexts, specifically Rumah Adat Kajang Leko. The objective was to train junior high school teachers to design interactive ethnomathematics-based media using Augmented Reality (AR) in order to foster deep learning and enhance digital competence. The program was conducted as community service in an onsite workshop at SMAN 8 Muaro Jambi, engaging lecturers, students, and partner teachers. A hands-on approach was applied, starting from the introduction of ethnomathematics concepts, E-COMATS design, AR feature integration, to the production of ready-to-use media. Findings revealed that more than 85% of teachers successfully produced AR-supported E-COMATS independently, while questionnaire results showed an increase in technological literacy with an average score of 4.35 out of 5. Participants perceived the developed media as relevant, innovative, and applicable in classroom practices. These results indicate that ethnomathematics-based E-COMATS training supported by AR is effective in improving teachers’ digital literacy and strengthening the integration of local culture into mathematics learning.Keywords: Augmented Reality, E-COMATS, Ethnomathematics, Junior High School Teachers, Technological Literacy ABSTRAKRendahnya literasi teknologi dan kemampuan guru dalam mengintegrasikan media pembelajaran digital masih menjadi tantangan utama dalam penerapan Kurikulum Merdeka. Untuk menjawab permasalahan tersebut, penelitian ini mengembangkan E-COMATS (Ethnomathematics Comic Augmented Reality for Teaching and Learning) berbasis konteks budaya lokal, yaitu Rumah Adat Kajang Leko. Tujuan kegiatan adalah melatih guru SMP agar mampu merancang media pembelajaran interaktif berbasis ethnomathematics dengan dukungan teknologi Augmented Reality (AR), sehingga dapat mendorong pembelajaran mendalam sekaligus meningkatkan kompetensi digital guru. Program dilaksanakan sebagai kegiatan pengabdian melalui workshop luring di SMAN 8 Muaro Jambi dengan melibatkan dosen, mahasiswa, dan guru mitra. Metode yang digunakan adalah praktik langsung mulai dari pengenalan konsep ethnomathematics, perancangan E-COMATS, integrasi fitur AR, hingga menghasilkan media siap pakai. Hasil menunjukkan lebih dari 85% guru berhasil menyelesaikan produk E-COMATS berbantuan AR secara mandiri, sedangkan hasil kuesioner memperlihatkan peningkatan literasi teknologi dengan skor rata-rata 4,35 dari skala 5. Guru menilai media yang dikembangkan relevan, inovatif, dan aplikatif dalam pembelajaran. Dengan demikian, pelatihan E-COMATS berbasis ethnomathematics berbantuan AR terbukti efektif dalam meningkatkan literasi digital guru sekaligus memperkuat integrasi budaya lokal dalam pembelajaran matematika.Kata Kunci: Augmented Reality, E-COMATS, Ethnomathematics, Guru SMP, Literasi Teknologi